"When the morning stars sang": essays in honor of Choon Leong Seow on the occasion of his sixty-fifth birthday - Seow, C. L.; Jones, Scott C.; Yoder, Christine Roy (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft 0934-2575, 2018)
During a moment of exponential growth and change in the fields of biblical and ancient Near Eastern studies, it is an opportune time to take stock of the state wisdom and wisdom literature with twenty-three essays honoring the consummate Weisheitslehrer, Professor Choon Leong Seow, Vanderbilt, Buffington, Cupples Chair in Divinity and Distinguished Professor of Hebrew Bible at Vanderbilt University. This Festschrift is tightly focused around wisdom themes, and all of the essays are written by senior scholars in the field. They represent not only the great diversity of approaches in the field of wisdom and wisdom literature, but also the remarkable range of interests and methods that have characterized Professor Seow's own work throughout the decades, including the theology of the wisdom literature, the social world of Ecclesiastes, the history of consequences of the book of Job, the poetry of the Psalms, and Northwest Semitic Inscriptions, just to name a few